The effect of mergers and acquisitions on cross-border banks with empirical evidence from China, involving both the Industrial and Commercial Bank of China and China Merchants Bank - Liu, Chang (2014)
Under the influence of the financial crisis, there is a great change in the structure of the world banking. China is less affected by the financial crisis, with the acceleration of the development of Chinese enterprises multinational, Chinese large commercial banks also speed up the internationalization, and there is a new wave of cross-border mergers and acquisitions in Chinese banking industry. This paper based on case study method, using event study and operating performance study, and using the Industrial and Commercial Bank of China buying the Standard Bank of South Africa and the China Merchants Bank purchasing the Hong Kong Wing Lung Bank as examples, to study the capital markets reactions for the merger announcement and changes in financial indicators before and after takeovers. The result shows that there is a significant positive cumulative abnormal return for both sides in merger and acquisition of the Industrial and Commercial Bank of China. However, there is a significant negative cumulative abnormal return in merger and acquisition of the China Merchants Bank. In addition, in the short term, these two cases of takeovers on the promotion of the level of profitability are not obvious. Finally proposed the Chinese large banks should focus on long-term gains, and actively expand overseas markets, optimize the allocation of resource, and enhance the ability to resist risks.